Critique 'Proceedings of a Symposium on Rare and Endangered Mollusks (Naiads) of the U.S. Columbus, Ohio 1971' - Billy G. Isom (Hello World!, 1973)
There is no disagreement with the purpose of the symposium on rare and endangered freshwater mollusks, but there is disagreement with the content of the proceedings and the fact that available expertise was not brought to bear on the problem. Correspondence with several eminent malacologists, including Dr. Henry van der Schalie. University of Michigan, revealed that none was invited to contribute to the symposium.